An appraisal of the student teachers' performance in the student teaching programme, College of Education, University of the Philippines, and its implications for Mahasarakam Teachers College in Thailand - Chuanpit, Thongtawee 1932- (s.n], 1971)
The purpose of this study was to determine whether the student teaching programme of the College of Education, University of the Philippines, is fulfilling the objectives for which it has been theoretically established. Documentary surveys, review of related literature and studies, and construction of evaluation criteria to measure actual performance were undertaken. The subjects involved were six college supervisors at the UP College of Education, 41 cooperating teachers in two laboratory schools, 5 cooperating schools in Quezon City, and 33 student teachers who have had experience in practice teaching, and to 25 college supervisors of Mahasarakam Teachers College including its 50 cooperating teachers and its 50 student teachers. It was revealed that there are common findings in both colleges on the functions of preparation, professional, guidance and community services.